President's Message: One Final Message - Farid, Donna (Operating Room Nurses Association of Canada Journal, 1999)
It seems strange to be writing this message as President of ORNAC, knowing that when it is published in the Canadian Operating Room Nursing Journal my term of office will be finished. The 16th National ORNAC Conference in Halifax, which I am chairing, will be behind us as well. I hope when those of you who attended the Conference are reading this back in your home provinces, you will have been enlightened, inspired, and will have a renewed commitment to become involved in promoting the role of the Perioperative Registered Nurse. I hope you will share this information and inspiration with your nursing colleagues who were unable to attend, and will encourage them to join you in your campaign. I also hope you will have found lasting memories of Halifax and the Maritimes.